Room-temperature fabrication of a delafossite CuCrO2 hole transport layer for perovskite solar cells. Issue 2 (11th December 2017) - Dunlap-Shohl, Wiley A.; Daunis, Trey B.; Wang, Xiaoming; Wang, Jian; Zhang, Boya; Barrera, Diego; Yan, Yanfa; Hsu, Julia W. P.; Mitzi, David B.
Abstract : A delafossite CuCrO2 hole transport layer deposited at room temperature from a nanoparticle suspension is used in efficient perovskite cells. Abstract : Delafossite oxides are promising hole transport layer (HTL) candidates for perovskite solar cells, due to their wide band gap, favorable energy band alignment relative to the perovskite absorber and simplicity of processing. In this paper, we investigate the properties of CuCrO2 (CCO) delafossite films using an integration of experimental and computational techniques. Phase-pure CCO films are deposited at room temperature by spin-casting suspensions of hydrothermally-synthesized nanoparticles, for use in a glass/ITO/CCO/CH3 NH3 PbI3 /C60 /BCP/Ag device structure. Although density functional theory (DFT) calculations predict an elevated hole effective mass along certain crystallographic directions, the nearly isotropic shape and small size of the CCO nanoparticles preserves transport properties within the films by randomizing particle orientation, preventing these unfavorable directions from dominating the film conductivity. Experimental measurements confirm that the CCO films display appropriate optical and electrical properties for use as an HTL, in good agreement with the DFT calculations. Solar cells made using these films exhibit stabilized power conversion efficiencies exceeding 14%, with only minor hysteresis in the current–voltage characteristics.